Analysis of Mathematics Curriculum Evaluation Studies Conducted in Turkey Between 2005-2023: A Systematic Review - Yavuzkan, Huriye; Tanrıseven, Işıl (Atlas Journal, 2024)
Curriculum evaluation studies are of great importance in thedevelopment of curricula and improvement of existing curricula. The aim of this study is to analyse the Mathematics Curriculum Evaluation studies conducted in Turkey between 2005 and 2023 in terms of methods, sample groups, data collection tools and techniques, findings and results, curriculum evaluation model used, and to give direction to future research and studies by gathering the studie sunder a single roof. For this purpose, the systematic review method was chosen because it will provide the opportunity to examine and evaluate the literature in a holisticway."Google Scholar" and "YÖK Thesis" databases were searched and the studies conducted in Turkey between the years 2005-2023 using thekey words "mathematicscurriculum" and "curriculumevaluation" were included in the study. The systematic review study was carried out on 19 studies, including 1 doctoral thesis, 4 master’s theses and 14 articles, which were determined with in the scope of the inclusion and exclusion criteria determined by the researchers. The data were analysed using the content analysis technique and the data summarisation form prepared by the researchers. In the study, the findings related to the research questions were discussed under five headings; scientific research method sused in curriculum evaluation studies, stakeholders as datasources, data collection techniquesused, results obtained from curriculum evaluation studies and curriculum evaluation models used. While the survey method was mostly used in the studies, it was found that interview forms, questionnaires and scales were frequently used as data collection tools and descriptive statistics were mostly used in data analysis. In addition, it is seen that teacher opinions are frequently used in mathematics curriculum evaluation studies. In most of the programmes evaluated in the studies, there were positive opinions about the programme in general and it was stated that some difficulties were encountered in practice. Considering all these, it can be said that in order for curriculum evaluation studies to achieve their goals, qualitative and quantitative research methods should be used together as much as possible to support each other, the process should be carried out in a multidimensional way by involving more than one stake holder in the studies, more than one data collection tool and technique should be used to describe and interpret the process, curriculum evaluation models that will provide a systematic frame work for evaluation studies should be used, and the curriculum should be reviewed according to the evaluation results and the faulty aspects should be arranged.